Patient information organization in the intensive care setting: expert knowledge elicitation with card sorting methods - Reese, Thomas (J Am Med Inform Assoc, 2018)
INTRODUCTION: Many electronic health records fail to support information uptake because they impose low-level information organization tasks on users. Clinical concept-oriented views have shown information processing improvements, but the specifics of this organization for critical care are unclear. OBJECTIVE: To determine high-level cognitive processes and patient information organization schema in critical care. METHODS: We conducted an open card sort of 29 patient data elements and a modified Delphi card sort of 65 patient data elements. Study participants were 39 clinicians with varied critical care training and experience. We analyzed the open sort with a hierarchical cluster analysis (HCA) and factor analysis (FA). The Delphi sort was split into three initiating groups that resulted in three unique solutions. We compared results between open sort analyses (HCA and FA), between card sorting exercises (open and Delphi), and across the Delphi solutions. RESULTS: Between the HCA and FA, we observed common constructs including cardiovascular and hemodynamics, infectious disease, medications, neurology, patient overview, respiratory, and vital signs. The more comprehensive Delphi sort solutions also included gastrointestinal, renal, and imaging constructs. CONCLUSIONS: We identified primarily system-based groupings (e.g., cardiovascular, respiratory). Source-based (e.g., medications, laboratory) groups became apparent when participants were asked to sort a longer list of concepts. These results suggest a hybrid approach to information organization, which may combine systems, source, or problem-based groupings, best supports clinicians’ mental models. These results can contribute to the design of information displays to better support clinicians’ access and interpretation of information for critical care decisions.